Simulation of large-strain behaviour of aluminium alloy under tensile loading using anisotropic plasticity models. (September 2015) - Khadyko, M.; Dumoulin, S.; Børvik, T.; Hopperstad, O.S.
Highlights: Tensile tests are performed on the AA6060 alloys in cast and extruded conditions. Extruded alloys with sharp textures demonstrate unusual fracture surface shapes. The material is modelled with crystal plasticity and anisotropic phenomenological plasticity. The tests are simulated by finite element models. Unusual shapes are reproduced using the simulation with crystal plasticity material model. Abstract: Cylindrical smooth and notched AA6060 samples were tested in tension. The material was either cast and homogenised or extruded with strong cube texture. The textured specimens demonstrated unusual shapes of the fracture surface that deviated from elliptical and were more rectangular in shape. A phenomenological plasticity model was used in finite element simulations of the tensile tests, together with a crystal plasticity model. The phenomenological plasticity model could not reproduce the evolution of the cross-section of the specimens made from the textured material. The crystal plasticity finite element model on the other hand demonstrated behaviour closer to the experiments.